2016
DOI: 10.1515/euco-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Small Towns in the Process of Urbanisation of the Wielkopolska Region (Poland)

Abstract: A study is made of the significance of small towns in the process of urbanisation of Wielkopolska, a region situated in the western part of Poland. The analysis is conducted in both, a dynamic and a static approach, and covers two aspects of urbanisation: demographic and spatial. The basic period examined embraces the years 2000-2015. What is visible in the set of Wielkopolska towns is the depopulation of its core city, Poznań, accompanied by an increase in the population of small units located in its suburban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…), and a closer look at the practices of postsocialist countries followed. Our analysis showed that in this region it was still -or again -becoming a noteworthy practice, with varying degrees of intensity, to elevate some constitutionally equal municipalities to a higher administrative level by individual and unquestionable decisions of central power (Konecka-Szydłowska, B. 2016;Veress, N.Cs.…”
Section: Introductionmentioning
confidence: 83%
“…), and a closer look at the practices of postsocialist countries followed. Our analysis showed that in this region it was still -or again -becoming a noteworthy practice, with varying degrees of intensity, to elevate some constitutionally equal municipalities to a higher administrative level by individual and unquestionable decisions of central power (Konecka-Szydłowska, B. 2016;Veress, N.Cs.…”
Section: Introductionmentioning
confidence: 83%
“…From the large number of literature sources, we extracted 22 studies focusing on the quality of life [16][17][18][19][20][21][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76], (see Table A1 in Appendix A). Since the empirical part of our research was aimed at towns located in the transborder area, we focused in particular on studies that are nationally recognized as important for Polish and German urban policy and research.…”
Section: Methodsmentioning
confidence: 99%
“…In the countries of Western Europe, functional and spatial transformations of the suburban area began many decades ago, but in the Central and Eastern part, these processes began much later and are related to the systemic transformation [1]. However, it seems that at present, trends are similar all over Europe, and suburban areas are subject to intensive spatial transformations [2][3][4][5][6][7][8][9][10], strong economic pressure [11][12][13][14] and landscape [15][16][17][18][19][20][21][22][23]. The areas near metropolitan centres, where migrations exert strong pressure, are the most transformed in Europe [24,25].…”
Section: Introductionmentioning
confidence: 99%